2007
DOI: 10.1007/s11123-007-0050-x
|View full text |Cite
|
Sign up to set email alerts
|

DEA-R: ratio-based comparative efficiency model, its mathematical relation to DEA and its use in applications

Abstract: DEA, Efficiency, Ratio analysis, Weight restrictions, C61, C14,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(16 citation statements)
references
References 16 publications
0
16
0
Order By: Relevance
“…Moreover, although the financial ratios method has rarely been used by scholars to assess and compare the performance of water industry companies, some researchers (Despic et al , 2007; Gonzalez‐Bravo, 2007) have recently proposed new tools which integrate financial ratios analysis with other methods, like DEA, revaluating the role of ratios for measuring efficiency. In addition, Feroz et al (2003) have shown that financial ratios analysis gives the same results as DEA if both are applied to the same sector.…”
Section: Research Questions and Methodologymentioning
confidence: 99%
“…Moreover, although the financial ratios method has rarely been used by scholars to assess and compare the performance of water industry companies, some researchers (Despic et al , 2007; Gonzalez‐Bravo, 2007) have recently proposed new tools which integrate financial ratios analysis with other methods, like DEA, revaluating the role of ratios for measuring efficiency. In addition, Feroz et al (2003) have shown that financial ratios analysis gives the same results as DEA if both are applied to the same sector.…”
Section: Research Questions and Methodologymentioning
confidence: 99%
“…When only ratio data of inputs to outputs or vice versa are available, conventional DEA models are not capable of evaluating the DMU. Furthermore, several studies were conducted in this field based on the idea of Despic et al (2007). The multiplier DEA-R with constant returns to scale assumption for evaluating DMU p , when only ratios y rj x ij are accessible, is given as follows: min θ p s:t:…”
Section: Cra Modelmentioning
confidence: 99%
“…There are some shortcomings in DEA such as the lack of access to input and output data and presence of the non-Archimedean « for input and output weighs, which leads to pseudo-inefficiency. To overcome such problems and to find more realistic and more available targets for DMUs, financial organizations and institutes are using DEA models based on ratio analysis (DEA-R) models (Despic et al (2007); Wei et al (2011aWei et al ( , b, c), (2012). Some further studies have also been conducted in this regard (Chen and Ali (2002); Emrouznejad and Amin (2009); Olesen et al (2015), ( 2017)), which indicates the significance of the subject.…”
Section: Introductionmentioning
confidence: 99%
“…As it is impossible to determine the 'absolute efficiency' that is evaluated based on the ideational datum point, the degree of efficiency is measured by comparing the units with a reference set that has identical input and output structure. 40 Considering a set of input and output variables, DEA provides a unified performance efficiency measurement (efficiency score) for each DMU. This measurement is completed by developing an empirically based 'best-practice' or efficient frontier as a result of an identified set of efficient DMUs (on the frontier) and inefficient DMUs (not on the frontier).…”
Section: Crs and Vrs Dea Techniquesmentioning
confidence: 99%